The Rehabilitation Influences of Therapeutic Exercises on the Neurological Focal Symptoms in Patients with Lumbosacral Spine Osteochondrosis - Olena Iakobson; Nataliya Greіda; Vladimir Lavryniuk; Oksana Hrytsay (Lesya Ukrainka Volyn National University, 2017)
Physical therapy of patients with lumbosacral osteochondrosis is the recent problem in clinical neurology, family medicine and kinesiotherapy. Dorsalgia is a prominent symptom of this disease, it has been observed at 40-80 % of population. Goal of research: to establish the effectivety of therapeutic exercises which are used for physical therapy of the lumbosacral osteochondrosis. Methods of research: analysis and compilation of modern scientific sources of information, clinical tests, statistical techniques. Research results: 44 patients, divided into control and experimental groups, participate in the research. Every group consists of 22 patients. All sick persons got pharmaceutical treatment after guideline for the diagnosis and treatment of vertebral osteochondrosis (MOZ Ukraine). Additionally the patients from experimental group had therapeutic exercises. All the patients estimated the pain intensity on the 1st and 10th day of therapy according to the VAS. On the same days the stretch symptoms were observed as the criteria of the state of lumbosacral spine. It was found the VAS score, determined on the 1st day, was statistical different in both group from the VAS score, determined on the 10th research day. During exam of Laseague sing it was established the data received on the 1st day were statistical different from the data received on the 10th day. Besides the Lasegue sing indexes obtained in the experimental group on the 10th day were statistic different from the same indexes in the control group. Summary. It is proved the combined use of the pharmaceutical treatment and the therapeutic exercises is more effective for pain relief and block of the neurological local signs than single pharmaceutical treatment at the patients with lumbosacral osteochondrosis.